Analisis Implementasi Hankamrata di Indonesia ditinjau dari Aspek Anggaran Pertahanan Negara - Evantino, Karolus; Sundari, Sri; Almubaroq, Hikmat Zakky; Sianipar, Leo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Defense and security are the main elements of the sustainability of a sovereign state with a variety of strategies that will be applied in accordance with national and even international dynamics. In formulating defense and security policies, national vigilance becomes a reference for various threats that go back and forth. Indonesia, which adheres to the Universal People's Defense and Security System (SISHANKAMRATA), has developed short and long-term defense strategies with efforts to optimize defense resources both in terms of infrastructure and technological and management adjustments. One of the main elements in developing potential defense resources is the source of funds or budget. In allocating the defense budget, the main concern is the creation, maintenance and equipping of the armed forces. The purpose of writing this article focuses on the concept and implementation of the Universal People's Defense System (SISHANKAMRATA) in terms of state defense budget management. The research method used is a literature study. The results of the literature study show that it is important for the government to make defense force development plans through sufficient and balanced budget allocations to create reliable defense capabilities. The program must be implemented in a transparent and accountable manner so that the available budget can be utilized as efficiently as possible for a utilization of the importance of a concept of defending the Unitary State of the Republic of Indonesia. Keywords: Defense, Sishankamrata, Defense Budget, Hankamrata.